Iatrogenic Hepatic Pneumovenogram - Govarthanan Rajendiran; Sulaiman Rathore; Gurmeet Sidhu; James Catevenis (Critical Care Research and Practice)
Accidental air entry during central venous catheterization is a preventable iatrogenic complication that can cause venous air embolism (VAE). Many cases of VAE are subclinical with no adverse outcome and thus go unreported. Usually, when symptoms are present, they are nonspecific, and a high index of clinical suspicion of possible VAE is required to prompt investigations and initiate appropriate therapy. Occasionally large embolism can lead to life-threatening acute cor pulmonale, asystole, sudden death, and arterial air embolism in the presence of shunt or patent foramen ovale. This paper discusses VAE during emergency central line placement and the diagnostic dilemma that it can be created in critically ill patients. All necessary precautions have to be strictly followed to prevent this iatrogenic complication.